Access to and adequacy of psychological services for adult patients in UK hospices: a national, cross-sectional survey - McInnerney, Daisy (BMC Palliat Care, 2021)
BACKGROUND: Providing psychological support to people living with terminal illness is a fundamental part of hospice care. Recent research on delivery of psychological services in hospices in the United Kingdom (UK) on a national level, including inequalities or variation in practice, is limited. A nationwide survey will highlight any differences in provision and in doing so help focus future research and inform best practice both within the UK, and internationally. The specific objectives of this survey are to (1) chart the types of psychological support available to adult patients in hospices in the UK in line with the National Institute for Health and Care Excellence model; (2) explore how services are organised; and (3) gather service perspectives on adequacy of care, and facilitators and barriers to appropriate practice. METHODS: A cross-sectional online survey emailed to adult hospices in the UK in November–December 2019. One staff member involved in the delivery and/or organisation of psychological support was invited to participate per hospice. Of 193 invited hospices, 116 took part. RESULTS: Sixteen percent rated their hospice psychological service as wholly adequate. The majority reported that services can access specialist professionals, but many relied on external referrals. Barriers to best practice included funding and staff capacity; facilitators included clear referral structures, audit and appropriate needs and outcome assessments. CONCLUSIONS: Access to psychological professionals has improved since the last survey 15 years ago, but the majority of responders felt their overall service was not wholly adequate. Basic emotional support is largely felt to be sufficient, but our results indicate a need for improvements in access to more specialist care. Partnerships with external mental health services may be key. Our findings highlight core facilitators and barriers to providing good psychological care at the end of life that should be considered by services both within the UK and on an international level. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12904-021-00724-3.